2010
DOI: 10.1007/s11242-010-9696-3
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Monitoring of Wettability Alteration by Silica Nanoparticles During Polymer Flooding to Heavy Oil in a Five-Spot Glass Micromodel

Abstract: It is well known that the oil recovery is affected by wettability of porous medium; however, the role of nanoparticles on wettability alteration of medium surfaces has remained a topic of debate in the literature. Furthermore, there is a little information of the way dispersed silica nanoparticles affect the oil recovery efficiency during polymer flooding, especially, when heavy oil is used. In this study, a series of injection experiments were performed in a five-spot glass micromodel after saturation with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 19 publications
(20 reference statements)
1
57
0
1
Order By: Relevance
“…Furthermore, it is highly desirable to change oil-wet surfaces more water-wet in carbon geo-sequestration projects to increase storage capacities and de-risk containment security [30,73]. Despite the vital importance for limestone reservoirs, previous studies focused on sandstone formations [21,25,26,28,41], and only limited information is available for carbonate reservoirs [40,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is highly desirable to change oil-wet surfaces more water-wet in carbon geo-sequestration projects to increase storage capacities and de-risk containment security [30,73]. Despite the vital importance for limestone reservoirs, previous studies focused on sandstone formations [21,25,26,28,41], and only limited information is available for carbonate reservoirs [40,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficiency of such formulations is a complex function of several factors, including the size and type of nanoparticles, nanofluid preparation and stability, the nature of the porous medium, thermo-physical and geological conditions and dwell time in the reservoir [39,40]. Despite the vital importance for limestone reservoirs globally, previous studies focused on sandstone formations [21,25,26,28,41], and only limited information is available for carbonate reservoirs: Roustaei and Bagherzadeh [42] conducted coreflood tests and they demonstrated that nanofluid-EOR can increase oil production by 9-17% depending on ageing time, and Zhang et al [40] have investigated the adsorption behaviour of silica nanoparticles on calcite powder.…”
Section: Introductionmentioning
confidence: 99%
“…In order to observe the microscopic behavior of polymer solutions with NPs in porous media, Maghzi et al [119,122] studied the performance of silica NPs in polyacrylamide solution in a five-spot glass micromodel saturated with heavy oil. They observed that the silica NPs caused an increase in oil recovery of polymer flooding by a factor of 10%, and strong water-wetting of the medium after flooding.…”
Section: Nano-assisted Polymer Floodingmentioning
confidence: 99%
“…Application of these Nanoparticles for enhancing oil recovery in water-wet sandstone systems is well documented in the literature (Ju et al 2002(Ju et al , 2006Ju and Fan 2009;Onyekonwu and Ologo 2010;Wang et al 2010). However, from the view of the literature in this field, only few papers address the application of these Nanoparticles in wettability alteration of carbonate systems (Maghzi et al 2011). In previous studies, the effect of Nanoparticles on oil-water interfacial tension and/or as an additive in waterflooding has not been investigated.…”
Section: Introductionmentioning
confidence: 99%